NUTRIENT MANAGEMENT STRATEGIES FOR MAIZE-POTATO-WHEAT CROPPING SYSTEM IN TYPIC USTOCHREPT SOILS - Khan, M A.; Shukla, Arvind K.; Upadhayay, N C; Singh, O P. (Potato Journal, 2013)
A field experiment was conducted in Typic Ustochrept soils of modipuram in order to find out best nutrient management strategy for optimum productivity of maize-potato-wheat cropping system. The yields of individual crop as well as potato equivalent yield were highest in treatment receiving 100% NPK through inorganic fertilizer. The treatment receiving recommended NPK along with secondary nutrient (Zn and S) did not show an edge over treatment getting100% NPK only. The yields of all the three crops were, invariably, 36-78% lower in organic treatment as compared to treatment receiving 100% recommended NPK through inorganic fertilizers. The organic carbon content has also increased in most of the treatment except control. In soil profile after harvest of two crop cycles, the NO3-N content was lower in organic manure supplied plots as compared to inorganic fertilizer.